Molecular Characterization of algD and TspE4.C2 Genes in Escherichia coli Isolated from Urinary Tract Infection Patients - AL-Badri , Zahraa Jamaal Al -Deen M. Shafeeq A.ALateef; Ibrahim, Souad Khalil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The current study collected 157 clinical samples from Iraqi patients suffering from urinary tract infections at various Baghdad hospitals, including Medical City/Educational Laboratories, Baghdad Teaching Hospital, Imamin Al-Kadhimiya Hospital, and the Central Children's Hospital in Baghdad, from 27 November 2022 to 11 January 2023. We identified and tested the formation of biofilms, which led to the detection of two genes, algD and TspE4.C2. Vitek 2 confirmed the final diagnosis after a biochemical and microscopic examination of 11 selected E. coli isolates. The Congo red method has detected the bacterial vulnerability to form biofilms. he findings of this study showed that all selected bacterial isolates formed the biofilm with a moderate degree (11 (100%)). The polymerase chain reaction (PCR) identified the algD and TspE4.C2 genes, demonstrating their significant role in biofilm production. The polymerase chain reaction results revealed the presence of the algD gene in 9 (81.8%) out of 11 isolates, while the TspE4.C2 gene was present in 10 (90.9%) isolates